The Main Problems that Arise in the Development of the Digital Economy and Their Solutions - Abror Rashidov R; Alakhonova Nafisa Lukhmonovna (Genius Journals, 2023)
Recent economic developments have evolved in a modern technological perspective. Consistent measures for the development of the digital economy are being implemented on the step-by-step introduction of electronic document circulation and e-commerce systems for providing services to individuals. the problems that arise during the development of the digital economy and the solutions to these problems are mentioned in this article.
Keywords: Digital economy; middle income